Criminal Liability for Traffic Accident Perpetrators with Schizophrenia - John Piter Tampubolon; Natsir Asnawi (Indonesian Journal Publisher, 2026)
The high number of traffic accidents in Indonesia is still narrowly understood as legal events oriented towards physical victims and material losses, while the psychological impact experienced by witnesses and indirect victims has not received adequate attention in the construction of criminal law. This condition becomes increasingly problematic when accidents involve perpetrators with mental disorders, particularly schizophrenia, because positive law does not provide clear and consistent regulations regarding criminal liability and the actions that can be imposed. The National Criminal Code, through Law Number 1 of 2023, does introduce the concept of action against perpetrators who are unable to take responsibility, but the use of the phrase